Development and application of an electronic treatment register: a system for enumerating populations and monitoring treatment during mass drug administration - William E. Oswald; David S. Kennedy; Jasmine Farzana; Saravanakumar Puthupalayam Kaliappan; Eloic Atindegla; Parfait Houngbégnon; Alvin Chisambi; Stefan Witek-McManus; Sean R. Galagan; Mira Emmanuel-Fabula; Marie-Claire; Hugo Legge; et al. (Taylor & Francis Group, 2020)
We developed an electronic treatment register for the DeWorm3 Project, a cluster-randomised, controlled trial in Benin, India, and Malawi testing the feasibility of interrupting transmission of soil-transmitted helminths through community-wide mass drug administration. The electronic treatment register was designed in xlsform, deployed via the SurveyCTO mobile data collection platform, and implemented on smartphones running the Android operating system. The versatile system enables collection of census and treatment status information, facilitates data aggregation and visualisation, and permits real-time feedback loops during implementation of mass drug administration. Here we describe the system's design and use within the DeWorm3 Project and key features, and by sharing the register here, we hope our readers will further explore its use within their research and disease-control activities.